Ecclesiological assumptions and international mission partnerships, a Philippine case study - Kruis, Stanley Dale (ProQuest LLC, 2009)
This dissertation employs five disciplinary lenses-historical, phenomenological, biblical, contextual-theological, and ecclesiological-to examine tensions in International Mission Partnerships. The study considers partnerships between churches and mission organizations based in Western countries and their counterparts in non-Western countries. A case study of the partnership between the Christian Reformed Church in the Philippines (CRCP) and Christian Reformed World Missions (CRWM) in church planting in the Philippines was conducted to identify partnership values and tensions. The study begins with an overview of the development of the International Mission Partnership (IMP) theme in Protestant mission history. A historical survey of the CRCP-CRWM partnership follows, leading to the case study. The data collection utilizes document review and semi-structured interviews with CRWM missionaries and CRCP church leaders. Grounded theory analysis generates seven major value-themes shared by the church leaders and missionaries. In further analysis. the study identifies two major partnership tensions underlying these value-themes: (1) tension between dominance and mutuality between partners, and (2) tension between local self-reliance and resource-sharing between partners. Three approaches are used in the theological portion of the dissertation: (1) Exploration of New Testament themes relevant for IMP, (2) Contextual (Filipino) theology and its relevance for IMP tensions, and (3) Ecclesiological analysis of assumptions underlying models of the Church. Four church models-institutional. community. servant, and house church-are examined to show the implications of the assumptions underlying these models for the two major IMP tensions. The ecclesiological analysis concludes that assumptions embedded in the institutional model of the Church have inevitably resulted in major IMP tensions. Other models of the Church can help overcome these tensions, although each model has its weaknesses. The study concludes with ten principles for understanding the church, and articulates their implications for addressing major IMP tensions. The study recommends that partners involved in IMP openly discuss with one another their experience of the partnership, reflect on how their partnership is impacted by their assumptions about the church, and go on to consider how the ten principles can re-shape their understanding of the church and address tensions they may experience in their partnership.--Abstract.